Topical oral cavity pharmacokinetic modeling of a stannous fluoride dentifrice: an unusual two compartment model - Scott, Douglas C; Coggan, John W; Cruze, Charles A; He, Tao; Johnson, Robert D (Journal of pharmaceutical sciences, 2009)
A pharmacokinetic model was developed describing the pharmacokinetics of stannous fluoride in human subjects after oral topical application of a stannous fluoride dentifrice. Twenty subjects participated in an investigation of an experimental dentifrice. Subjects rinsed their mouths with the experimental dentifrice slurry. Saliva and plaque samples were obtained from the subjects at various times up to 6 h after administration. Samples were analyzed for total tin content, used as an analytical marker for the active stannous fluoride ingredient, using a graphite furnace atomic absorption spectrometer. The modeling indicates that there is an obvious kinetic relationship between saliva and plaque compartments and that stannous fluoride is very well retained in and slowly released from plaque (and oral surfaces) into saliva. Additionally, both compartments are simultaneously loaded during administration unlike typical systemic drug behavior, and the elimination rate "constant" from the central compartment (saliva) changes due to changes in salivary flow. Stannous fluoride is cleared from saliva rapidly but very well retained in gingival plaque. The model with simultaneous loading of plaque and saliva describes these observations and may account for the prolonged antiplaque and antigingivitis benefits of stannous fluoride.